Increased CD64 expression on polymorphonuclear neutrophils indicates infectious complications following solid organ transplantation - Grey, Daniel; Sack, Ulrich; Scholz, Markus; Knaack, Heike; Fricke, Stephan; Oppel, Christoph; Luderer, Daniel; Fangmann, Josef; Emmrich, Frank; Kamprad, Manja (Cytometry. Part A : the journal of the International Society for Analytical Cytology, 2011)
The aim of this study was to evaluate the diagnostic value of monitoring CD64 antigen upregulation on polymorphonuclear neutrophils (PMN) for the identification of infectious complications in the postoperative course of solid organ transplanted patients. Twenty-five kidney, 13 liver, and four pancreas-kidney transplanted patients were included. Beginning with preoperative values up to postoperative values after 3 months for each patient, the PMN CD64 Index, HLA-DR on monocytes, NKp44+ NK and NK/T cells, CXCR3+ NK cells, CXCR3+ T helper cells, CXCR3+ NK/T cells, and CD4/CD8 ratio were measured by flow cytometry. Subsequently they were correlated with confirmed postoperative complications. Measuring the PMN CD64 Index reached a sensitivity of 89% and a specificity of 65% in the detection of infectious complications. Concerning this matter, it was a significantly better marker than all other included parameters except CXCR3+ NK/T cells. In contrast, according to our results the PMN CD64 Index has no diagnostic relevance in detection of rejections. The combination of included parameters showed no improved diagnostic value. Due to its high sensitivity and specificity for infectious complications CD64 on PMN could be proven a very good indicator in evaluating suspected infectious complications in the postoperative course of transplanted patients. The aim of this study was to evaluate the diagnostic value of monitoring CD64 antigen upregulation on polymorphonuclear neutrophils (PMN) for the identification of infectious complications in the postoperative course of solid organ transplanted patients. Twenty-five kidney, 13 liver, and four pancreas-kidney transplanted patients were included. Beginning with preoperative values up to postoperative values after 3 months for each patient, the PMN CD64 Index, HLA-DR on monocytes, NKp44+ NK and NK/T cells, CXCR3+ NK cells, CXCR3+ T helper cells, CXCR3+ NK/T cells, and CD4/CD8 ratio were measured by flow cytometry. Subsequently they were correlated with confirmed postoperative complications. Measuring the PMN CD64 Index reached a sensitivity of 89% and a specificity of 65% in the detection of infectious complications. Concerning this matter, it was a significantly better marker than all other included parameters except CXCR3+ NK/T cells. In contrast, according to our results the PMN CD64 Index has no diagnostic relevance in detection of rejections. The combination of included parameters showed no improved diagnostic value. Due to its high sensitivity and specificity for infectious complications CD64 on PMN could be proven a very good indicator in evaluating suspected infectious complications in the postoperative course of transplanted patients.